Gender Analysis of Hadith on the Virtues of Women's Shaf in Congregational Prayer in the Modern Context - Junaid, Junaid bin; Lutfiah, Winona (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2024)
This article aims to examine how the hadith regarding women's shaf in congregational prayer can be analyzed through a gender perspective. The approach used is qualitative, focusing on descriptive-analytical methods, while the data analysis technique employed is content analysis with an emphasis on gender analysis. The findings of this study indicate that using a gender analysis allows the hadith to be understood in a way that does not discriminate against women and offers a more egalitarian perspective on the arrangement of men's and women's shaf. In the modern context, such rules are not perceived as discriminatory, and religious teachings can be detached from patriarchal imagery. This research recommends further exploration by academics and is expected to serve as an additional reference for studies on hadith related to women's and men's shaf in congregational prayer.